(untitled) (Bangladesh Journal of Medicine, 2016)
This cross-sectional study was conducted to evaluate the individual awareness, related risk factors and complications of diabetes with socio-demographic profiles of the study individuals in Noakhali region, Bangladesh during June to December, 2013. A total 250 participants were selected randomly and data were collected using structured questionnaire. Among the respondents 47.20% were found male and 52.80% were female and majorities (52.00%) of the respondents were urban people. Respondents completed secondary study level or below were the dominant group. 9.20%, 27.20%, 12.80% and 34.40% respondents were agriculturist, businessman and housewives respectively. Women showed better knowledge about overall diabetes (20.00%) and blood glucose level (9.60%), in case of causes, symptoms and management men (12.80%, 23.20% and 18.40% respectively) were found dominant than women (10.00%, 16.00% and 12.00% respectively). It was found that 13.20% respondents were suffering from impaired glucose tolerance and 79.20% had diabetes mellitus where female were more vulnerable than male. Family history was found the significant risk factor (p= 0.016; Ç2 = 5.849) for diabetes (total 62%, male 40.65% and female 59.35%), Other risk factors like age (67.20%), obesity (46.40%), hypercholesterolemia (82.00%), excess triglyceride (78.00%) and hypertension (29.60%) remained insignificant respectively and in every cases female were found more vulnerable than men. Study revealed that knowledge regarding diabetes was not up to the mark to the respondents though it is now one of the most pandemic diseases in the world. Bangladesh J Medicine Jan 2016; 27(1) : 8-15